KERAGAMAN APLIKASI PSAK 24 (REVISI 2004) TENTANG IMBALAN KERJA DALAM KAITANNYA DENGAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Maswar Patuh Priyadi; Sugeng Praptoyo (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
The purpose of this article is to explain application of PSAK 24 (revised) at the first year at three different business organization. Post employment benefit is employee’s benefit gived by firm at the time retirement happened. Post employment benefit can be payed to employee directly by unfunded or funded. Funding can be done with pension fund or assurance of employees. Aplication of PSAK 24 (revised 2004) at the first year will decrease earnings and then decrease distribution of dividen. Besides application diversity of PSAK 24 (revised) was caused by management policy to choose payment to employee whether with funded or unfunded, and also caused by management policy to choose actuaria assumptions and another management policy.